La crise de Berlin de 1961 - Legault, Albert (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
The Berlin Wall was but an episode in what is referred to as the Berlin Crisis of 1961. The latter's context included two other conflicts : a domestic power struggle within the Soviet Union and a race for strategic superiority between the superpowers. The methodology employed makes it possible to show that the Berlin Crisis constituted a hiatus within the much larger conflict of the Cold War. It also reveals that the frequency with which objectives were formulated constitutes a very important « indicator » « reference point » or « signpost » within the crisis process. These findings would tend to demonstrate that the stimulus-response model, nothwithstanding its importance, should be completed by a much more methodical examination of the evolution of the objectives pursued by a State in the conduct of its foreign relations.